Penerapan Pengujian Website Siapkerja Menggunakan Uji Alpha Dan Beta - Adiansyah, Ramadhan; Rifqi Zain, Dhiya; Danish Aqeela, Khansa; Mubarak, Kevin; Aldhyansyah, Putra (CV. Shofanah Media Berkah, 2024)
In the digital era, online job search has become an important necessity. The implementation of UU No. 23 of 2014 on Regional Government requires high levels of cooperation and coordination between the central and regional governments in the field of labor. The SIAPkerja website is here to help job seekers find suitable opportunities. Alpha and beta testing was conducted to ensure the quality and stability of the site. Alpha testing uses the black box method to check the function of features, while beta testing involves end users in evaluating the experience. Alpha testing results found some bugs that needed to be fixed, while beta testing scored an average of 80%, indicating the site was fit for use. Recommendations include fixing buttons that don't work, developing features that are not yet optimised, and periodic testing to ensure quality. The goal is to create a platform that is stable, functional, and optimally meets user needs.